How Simi got her groom back : a novel - Dev, Sonali (Lake Union Publishing, 2026)
The Naik sisters escaped their traumatic past in Mumbai to come to the States, but their journeys have been vastly different. Simi is working toward a bright future as a pediatric nurse in a small town in Kentucky when Rupi shows up at her door in distress, on the run, and as always, dragging trouble in her wake. With Rupi's safety in jeopardy, the sisters hatch a desperate plan to keep her in the country: Rupi must get married and fast even if it means Simi recruiting the man she's been secretly dating as her sister's groom. A perfect plan? Not quite. But there aren't many alternatives. As the big day inches closer, Simi and Rupi face a storm of wedding shenanigans and romantic surprises, not to mention sisterly jealousies. As the stakes and tensions rise, will their secrets tear them apart or will they find a way to risk everything for love? --from Amazon.